Legal Protection of Health Workers and its Implications for Service Quality and Patient Satisfaction - Maya Sari, Vera; Susanti, Reni; Suparman, Odang (Jurnal Ilmiah Dunia Hukum, 2025)
Violence, legal threats, and professional risks faced by healthcare workers in Indonesia remain a concern despite the existence of statutory legal protections. Law Number 17 of 2023 on Health and Law Number 36 of 2014 on Health Workers normatively guarantee legal protection for healthcare personnel, however, empirical studies examining how such protection influences service performance and patient satisfaction are still limited. This study aims to analyze the relationship between legal protection for healthcare workers, service quality, and patient satisfaction at Dr. Achmad Mochtar Bukittinggi Regional General Hospital, with a focus on the mediating role of service quality. The study employs a normative–empirical (socio-legal) research design using a quantitative correlational approach. Data were collected through structured questionnaires from 238 healthcare workers and 800 patients and analyzed using descriptive statistics, Pearson correlation, multiple regression, and mediation analysis. The results show that legal protection is perceived as fairly good, service quality as good, and patient satisfaction as high. Legal protection has a significant positive relationship with service quality, while service quality strongly influences patient satisfaction and mediates the effect of legal protection. The study concludes that effective implementation of legal protection contributes indirectly to patient satisfaction by improving service quality.